Harnessing Artificial Intelligence: Balancing Opportunity with Ethical and Regulatory Responsibility - Chilcott, Glenn (Global journal of Business and Integral Security, 2026)
Artificial intelligence (AI) is poised to deliver transformative economic and societal benefits, with projections suggesting it could contribute up to 15.7 trillion to the global economy by 2030. Generative AI alone is expected to create trillions of dollars in annual value across industries. Yet these opportunities are accompanied by profound ethical, regulatory, and governance challenges, including bias, privacy risks, market concentration, and environmental impacts. This paper examines the opportunities and risks of AI, the mechanisms for mitigating those risks through legislation, regulation, and organisational governance, and the importance of embedding ethical principles in AI’s design and deployment. It concludes with an assessment of recent developments and forward-looking predictions for the next one to five years, underscoring the urgent need for a coordinated global response that balances innovation with responsibility.